Meningkatkan Kreativitas Matematik dan Kepercayaan Diri Siswa melalui Pembelajaran Humanistik Berbasis Pendidikan Matematika Realistik - Lia Rista; M. Ikhsan; Hizir Hizir (Didaktik Matematika, 2016)
The purpose of this study was to determine the difference between the improvement of mathematical creativity and self-confidence of students after PMR-based humanistic learning based on student level (high, medium, and low), and interaction between the learning levels of students after application of humanistic learning with PMR based on mathematical creativity of students. This study used a purely experimental research with research design shaped in "pre test - post test". The samples of this study were randomly choosen, and two classes were taken, namely class X-MIA4 as the experimental class (PMR-based humanistic learning), while class X-MIA7 as the control class (conventional learning). The instrument used was a mathematical creativity tests and questionnaires of self-confidence. The statistical test (the t-test of independent sample t-test) was used to analyze the data. The results showed that there were differences increase between mathematics creativity and self-confidence of students after the applied learning humanistic-based PMR and students who received conventional learning, both overall and by subgroups, and there was an interaction between the learning strategies and subgroups of students (high, medium and low) to creativity math students.